(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article meticulously examines the significance of natural resources in the context of our nation’s development while emphasizing the critical need for their sustainable utilization. It adeptly outlines the diverse range of natural assets our country possesses and underscores the looming threats posed by their unchecked exploitation.The annotation elucidates the pressing challenges faced due to unsustainable practices and highlights the multifaceted implications, including environmental degradation, loss of biodiversity, and the exacerbation of climate change. Moreover, it aptly proposes a strategic framework encompassing various measures imperative for the prudent management of these resources.